Analisis Tingkat Kesulitan Soal Pemecahan Masalah Dalam Buku Siswa Matematika Wajib SMA Kelas X Kurikulum 2013 - Pangesti, Laras Tunjung; , Idris Harta, M.A., Ph.D (2017)
This study aims to analyze and describe the level of difficulty of problem solving item mathematics in terms of the components of matter: the type of problem, the type of number, type of operation, many operations, many questions, the adequacy of the data and the similarity with the revious problem in the Matematics student book required high school grade X curriculum 2013. This research conducted by matching the predetermined rule on matters of mathematical problem solving that is contained in the book. This study used qualitative research. The methods of collection date used were observation on the sample of every questions and documentation. The date were analyzed using workflow stage data reduction, data presentation, and conclusion. The results showed include: 1) There are 31 problem solving or approximately 16,32% of the 190 items. 2) a matter of solving the kind of routine problems, 3) Types of numbers that are used in problems solving such as: number count with of 41,94%, negative numbers with of 12,90%, with a decimals 19,35%, fraction number of 25,81%. 4) Types of operations used in solving problems such as: the addition operation and reduction operation with a of 77,42%, type multiplication operation with a of 90,32%, this type of surgery division with 51,61%. 5) Many questions that exist when it comes to problems solving such as: 35,48% about one question and about or approximately 70,91% have more than one question. 6) about the adequacy of problem solving has complete data. 7) imilarity about the previous problem was 35,48% similar and questions that are not similar to the previous approximately 64,52%. 8) these problems solving fall into three categories, namely the level of difficulty about 22.58% lower categories, the categories were 35.48% and 41.94% higher category.